1998
DOI: 10.1007/s100510050521
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the critical behaviour of fracture precursors

Abstract: Abstract. The statistical properties and the localization of fracture precursors on heteregeneous materials is studied by recording their acoustic emission as a function of the applied load. It's found that the microcrack cluster together as the load increases and the instantaneous acoustic energy has an invariant power law distribution. The integrated acoustic energy presents a critical divergency close to the failure load for the sample. These result support the idea that fracture can be viewed as a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
183
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(219 citation statements)
references
References 35 publications
(34 reference statements)
31
183
2
3
Order By: Relevance
“…The so-called steady state viscoplastic deformation is, in fact, shown to occur in bursts of relaxation following a power law distribution of energy and time separation. Such power law behavior is suggestive of a critical dynamics of dislocations, similar to those argued for microfracturing [Petri et al, 1994;Guarino et al, 1998]. …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The so-called steady state viscoplastic deformation is, in fact, shown to occur in bursts of relaxation following a power law distribution of energy and time separation. Such power law behavior is suggestive of a critical dynamics of dislocations, similar to those argued for microfracturing [Petri et al, 1994;Guarino et al, 1998]. …”
Section: Introductionsupporting
confidence: 59%
“…In the present paper, we propose to embed these earlier results in the more general framework of critical systems. Such a critical framework has been recently proposed to describe brittle fracturing [e.g.,Hermann and Roux, 1990;Andersen et al, 1997], fromthe laboratory sample scale [Petri et al, 1994;Guarino et al, 1998] to the earth crust scale [Main, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to the study of critical phase transitions in statistical physics, it has been recently argued that the fracture of heterogeneous materials could be viewed as a critical phenomenon (Herrmann and Roux, 1990;Vanneste and Sornette, 1992;Lamaignere et al, 1996;Andersen et al, 1997;Sornette, 2000), either at laboratory scale (Petri et al, 1994;Guarino et al, 1998Guarino et al, , 2002 or at geophysical scales (Chelidze, 1982;Allegre et al, 1982;Sornette and Sornette, 1990;Diodati et al, 1991;Sornette and Sammis, 1995;Saleur et al, 1996a,b;Main, 1996;Bowman et al, 1998;Kossobokov et al, 1999). This result comes from different observations including power law scaling in space (fractals), time and energy, long-range correlations, or the divergence of the rate of energy dissipation near the critical point.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers investigated the elastic energy release during the failure process of materials [17][18][19][20][21][22][23][24]. They all observed that the energy release accelerated following a power law.…”
Section: Introductionmentioning
confidence: 99%